Decomposed Coconut Compith - a Good Nursery Media Mix for Eucalyptus Spp. - Kumar, A.; Marimuthu, T. (Indian Forester, 1997)
Among the six media mixes tested, the DCCP 50 and DCCP 25 increased the vigour, dry matter and number of secondary leaves of E. camaldulensis and E. tereticornis seedlings both in nursery and containers.